The role of clinical and neuroimaging features in the diagnosis of CADASIL - Bersano, Anna; Grond-Ginsbach, Caspar (Journal of neurology, 2018)
BackgroundCerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common familial cerebral small vessel disease, caused by NOTCH3 gene mutations. The aim of our study was to identify clinical and neuroradiological features which would be useful in identifying which patients presenting with lacunar stroke and TIA are likely to have CADASIL.MethodsPatients with lacunar stroke or TIA were included in the present study. For each patient, demographic and clinical data were collected. MRI images were centrally analysed for the presence of lacunar infarcts, microbleeds, temporal lobe involvement, global atrophy and white matter hyperintensities.Results128 patients (mean age 56.3 ± 12.4 years) were included. A NOTCH3 mutation was found in 12.5% of them. A family history of stroke, the presence of dementia and external capsule lesions on MRI were the only features significantly associated with the diagnosis of CADASIL. Although thalamic, temporal pole gliosis and severe white matter hyperintensities were less specific for CADASIL diagnosis, the combination of a number of these factors together with familial history for stroke result in a higher positive predictive value and specificity.ConclusionsA careful familial history collection and neuroradiological assessment can identify patients in whom NOTCH3 genetic testing has a higher yield.
Gesehen am 08.08.2019